A practical model for sunlight disinfection of a subtropical maturation pond. (1st January 2017) - Dahl, N.W.; Woodfield, P.L.; Lemckert, C.J.; Stratton, H.; Roiko, A.
Abstract: Maturation ponds are a type of waste stabilisation pond (WSP) designed to reduce carbon, nutrients and pathogens in the final stages of a WSP wastewater treatment system. In this study, a one-dimensional plug-flow pond model is proposed to predict temperature and E. coli concentration distributions and overall pond disinfection performance. The model accounts for the effects of vertical mixing and ultraviolet light-dependent die-off rate kinetics. Measurements of radiation, wind-speed, humidity and air temperature are recorded for model inputs and good agreement with measured vertical temperature distributions and outlet E. coli concentrations is found in an operational, subtropical maturation pond. Measurements and the model both show a diurnal pattern of stratification during daylight hours and natural convective mixing at night on days corresponding to low wind speeds, strong heat input from solar radiation and clear night skies. In the evenings, the thermal stratification is shown to collapse due to surface energy loss via longwave radiation which triggers top-down natural convective mixing. The disinfection model is found to be sensitive to the choice of die-off kinetics. The diurnal mixing pattern is found to play a vital role in the disinfection process by ensuring that pathogens are regularly transported to the near-surface layer where ultraviolet light penetration is effective. The model proposed in this paper offers clear advantages to pond designers by including geographical specific, time-varying boundary conditions and accounting for the important physical aspects of vertical mixing and sunlight inactivation processes, yet is computationally straightforward. Graphical abstract: Highlights: A practical model for the prediction of E. coli die-off is proposed. Vertical sunlight inactivation and mixing is accounted for. Stratification isolates bottom pathogens from sunlight. Night-time mixing redistributes pathogens for following day. Transient boundary conditions reproduce effects of observed weather conditions.